Laparoscopic liver resection of segment seven: A case report and review of surgical techniques. (2020) - Takagi, Kosei; Kuise, Takashi; Umeda, Yuzo; Yoshida, Ryuichi; Teraishi, Fuminori; Yagi, Takahito; Fujiwara, Toshiyoshi
Highlights: Laparoscopic liver resection of segment 7 (LLR-S7) is technically challenging procedure. Various laparoscopic approaches for S7 have been reported. Sufficient knowledge on various approaches for S7 is needed to perform LLR-S7 safely. Our experience and a literature review on surgical techniques of LLR-S7 are demonstrated. Abstract: Introduction: Laparoscopic liver resection of segment seven (LLR-S7) is a technically challenging procedure due to its anatomical location and difficult accessibility. Herein, we present our experience with LLR-S7, and demonstrate a literature review regarding surgical techniques. Presentation of case: A 28-year-old female was diagnosed with rectosigmoid cancer and synchronous liver metastases at the segment three (S3) and S7, which were treated with laparoscopic procedure. After the completely mobilization of the right lobe, the Glissonean pedicle of S7 (G7) was intrahepatically transected. The right hepatic vein was exposed to identify the venous branch of S7 (V7). Finally the liver parenchyma between RHV and dissection line was divided. Discussion: Various laparoscopic approaches for S7 have been reported including the Glissonian approach from the hilum, the intrahepatic Glissonean approach, the caudate lobe first approach, and the lateral approach from intercostal ports. To perform LLR-S7 safely, it is important to understand the advantage of each technique including the trocar placement and approaches to S7 by laparoscopy. Conclusion: We present our experience of LLR-S7 for the tumor located at the top of S7, successfully performed with the intrahepatic Glissonean approach. LLR-S7 can be performed safely with advanced laparoscopic techniques and sufficient knowledge on various approaches for S7.